Desenvolvimento de métodos analíticos para determinação de arsênio, cádmio, cobre, mercúrio e chumbo em mel - Heulla Pereira Vieira (2012)
In this work, some methods were developed for analysis of metals of significant toxicity, such as mercury, arsenic, lead, copper and cadmium in honey, capable of simplifying some methods currently in use. Two analytical methods employing Cold Vapor Atomic Absorption Spectrometry (CVAAS) and a Direct Mercury Analyzer (DMA) were optimized and validated to determine the Hg concentration in honey samples. The CVAAS method consisted of preparing solutions containing 5.0% (w/v) honey, 4.0% (v/v) H2O2 and 6.0% (v/v) HNO3. Hg determination was accomplished by treatment with 0.6% (w/v) NaBH4 in 0.5% (w/v) NaOH and 6.0 mol/L HCl. In the DMA method, measurements were made using up to 100 mg of honey sample without any prior treatment. The drying and decomposition times along with drying temperature were optimized. In the development of the method for determination of arsenic in samples of honey, the variables studied in the optimization of the method were NaBH4 concentration, pre-reducing agent, HCl concentration, the diluents type and contact time with the sample. The optimized conditions were 5.0 % (w/v) of sample prepared in 1.3 mol/L HCl and 1.0 % (w/v) SC(NH2)2. The hydride generation solutions were 0.85 % (w/v) NaBH4 and 2.5 mol/L HCl. After validation, the methods were used to quantify Hg in 35 honey samples, collected from several cities in Minas Gerais, Brazil. All honey samples showed Hg concentrations below 1.0 g/kg and As concentrations below 20 g/kg. The proposed methodologies do not require a pre-treatment of digestion of the sample, so they can be considered more efficient, fast, with low cost reagents and without problems of volatility losses of the elements of interest. A method using thermospray flame furnace fast sequential atomic absorption spectrometry (TS-FF-FS-AAS) was developed in order to determining Cd, Cu and Pb in honey. During the development of the method, the effects: nickel tube length and quantity of holes, flow of the sample and signal acquisition mode, were studied. Then, the effects of time and temperature of extraction and the reagents HNO3, HCl and H2O2 were studied using factorial and central composite designs. The optimized conditions were: prepare of 50 mL of solution containing 1.0 g of sample, 2.0 mL of HNO3 and 1.0 mL of H2O2, digested in a block with heating until the temperature of 128 +- 5 °C for 30 minutes. Aftervalidation, the limits of detection were 0.010 mg/kg (Cd), 1.0 mg/kg (Cu) and 0.10 mg/kg (Pb), meeting the intended purpose of using TS-FF-FS-AAS for determination of Cd, Cu and Pb in honey in attendance to the maximum limits required by Brazilian legislation (1998) and Common Market of the South (MERCOSUR, 2011). For the 35 studied samples, it was possible to determine above the limits of detection: Cu in one sample, obtaining 1.1 mg/kg, and lead in two samples: 0.14 mg/kg and 0.17 mg/kg. For cadmium, all samples had concentrations below 0.010 mg/kg. It is noteworthy that there was a gain in sensitivity with the use of TS-FF-FS-AAS of 67.2, 3.4 and 72.8 times for the Cd, Cu and Pb, respectively, relative to FAAS. The TS-FF-FS-AAS had contributed to a gain of time of thrice, in relation to mono-element equipment (TS-FF-AAS), reducing the costs of this analysis.